Designing User Interface and User Experience for Habit Tracker Application for Android Mobile Devices - Natalia, Nila (Journal Collabits, 2025)
Positive habit formation is one of the main challenges in everyday life that requires consistency and continuous motivation. This study aims to design and develop an Android-based habit tracker application with a focus on optimizing the User Interface (UI) and User Experience (UX) to increase user engagement and effectiveness in building positive habits. The research methodology uses the User-Centered Design (UCD) approach which includes the stages of user needs analysis, wireframe and mockup design, prototyping, and usability testing evaluation. Data collection was carried out through a survey of 150 respondents to identify user needs and preferences for the habit tracker application. The UI/UX design process integrates the principles of Material Design Guidelines and the psychology of habit formation theory to create an intuitive and motivating interface. The main features of the application include habit tracking with progress visualization, reward and gamification systems, reminder notifications, and analytics dashboards. The results of the usability testing evaluation showed a user satisfaction level of 87% with a System Usability Scale (SUS) score of 82.5, which is included in the